2021
DOI: 10.1093/ptj/pzab170
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Electrical Stimulation Improves Muscle Strength, Biomechanics of Movement, and Functional Mobility in Children With Chronic Neurological Disorders: A Systematic Review and Meta-Analysis

Abstract: Objective Chronic neurological disorders (CND) generally produce deleterious effects on the musculoskeletal system and can affect physical activity and increase sedentary behavior in children, hindering the execution of training programs and the attainment of a correct dose of exercise. The purpose of this systematic review is to analyze the effect of NMES on skeletal muscle and then on biomechanics of movement, functional mobility, strength, spasticity, muscle architecture, and body composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Applying NMES during the casting periods in our study helped counteract the significant decrease in strength, thus resulting in improved gait function. These findings are further supported by Cobo-Vicente et al., 42 who have reported that NMES enhances muscle strength, functional mobility, and movement biomechanics in children with CP. Furthermore, recent evidence from systematic reviews and other studies supports using NMES for strengthening in individuals with spastic CP, to improve mobility and gross motor function, and safely induce restorative changes.…”
Section: Discussionsupporting
confidence: 77%
“…Applying NMES during the casting periods in our study helped counteract the significant decrease in strength, thus resulting in improved gait function. These findings are further supported by Cobo-Vicente et al., 42 who have reported that NMES enhances muscle strength, functional mobility, and movement biomechanics in children with CP. Furthermore, recent evidence from systematic reviews and other studies supports using NMES for strengthening in individuals with spastic CP, to improve mobility and gross motor function, and safely induce restorative changes.…”
Section: Discussionsupporting
confidence: 77%
“…Rehabilitation should incorporate the treatment supporting nerve regeneration, muscle strengthening, and maintaining functional ranges of motion of the injured extremities. It comprises the neuromuscular electrical stimulation (NMES) [12,34,35]. Contemporary researches show that NMES increases the strength of stimulated muscles, thereby preventing atrophy while waiting for the results of axonal regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to other types of electrotherapy that have been shown to be effective in improving spasticity such as neuromuscular electrical stimulation NMES [55,56], RPMSinduced pain is significantly less than NMES-induced pain, even when using the same stimulation intensity [57]. Therefore, RPMS simultaneously provides stronger stimulation than NMES and limits pain [58].…”
Section: Discussionmentioning
confidence: 99%